THE ROLE OF THE NOTARY IN MAKING AUTHENTIC DEED ON THE CHANGE OF NAME IDENTITY - R. Juli Moertiono (Kanun Jurnal Ilmu Hukum, 2022)
Notaries, in carrying out their functions, are required to recognize the person presence in order to prevent falsification of identity, so the principle of caution is needed. The issue of name changes, identity, and the role of the Notary in making authentic deeds need to be studied from a legal perspective. The research method used is normative. Meanwhile, data collection tools were carried out using data collection tools, namely: 1) literature study, and 2) documentary study.  Collecting secondary data related to the problems raised, by studying books, legal journals, research results and statutory regulatory documents. The research results show that there is a role for the Notary in making authentic deeds regarding name identity changes. In this way, it can provide legal certainty for someone who applies for a change in name identity for some reasons. Notary should be more caution in ensuring the validity of identity in making a deed.